IMPLEMENTASI KEBIJAKAN KETAHANAN PANGAN DI KOTA PEKANBARU - Husein, Pratiwi Rahmamilania; Yuliani, Febri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This study aims to determine the strengthening of food security towards food independence in Pekanbaru City and to determine the factors that influence in strengthening food security towards food independence in Pekanbaru City. This research is a study that uses a qualitative methodology. This research is descriptive, describing the reality correctly regarding strengthening food security towards food independence in Pekanbaru City. The results of this study are strengthening food security towards food self-sufficiency in Pekanbaru City carried out by optimizing the yard of the house by the Women Farmers Group (WFG), optimizing idle land by the Farmer Group (FG), providing seeds and fertilizer assistance to WFG and FG. Also institutional and community empowerment, monitoring information on basic food prices. Encouraging non-rice local food processing into processed food products while still paying attention to safety and nutritional quality, planting corn with women farmer groups. Keywords : Strengthening, food security, food independence